Better outcome for parotid versus neck metastasis of head and neck cutaneous squamous cell carcinoma: a new report on reemerging data - Girardi,Fábio Muradás (2021)
Abstract Introduction Regional metastases of cutaneous head and neck squamous cell carcinoma occur in approximately 5 % of cases, being the most important prognostic factor in survival, currently with no distinction between parotid and neck metastasis. Objective The purpose of this study was to evaluate the prognostic features among patients with head and neck cutaneous squamous cell carcinoma exhibiting regional metastasis. Methods A retrospective analysis of patients with cutaneous squamous cell carcinoma who underwent parotidectomy and/or neck dissection from 2011 to 2018 at a single institution tertiary center was performed. Patient demographics, clinical, surgical and pathological information, adjuvant treatments, and outcome at last follow-up were collected. Outcomes included disease recurrence and death due to the disease. Prognostic value of clinic pathological features associated with disease-specific survival was obtained. Results Thirty-eight cases of head and neck cutaneous squamous cell carcinoma with parotid and/or neck metastasis were identified. Overall, 18 (47.3 %) patients showed parotid metastasis alone, 12 (31.5 %) exhibited neck metastasis alone and 8 (21.0 %) had both. A primary tumor in the parotid zone (Hazard Ratio ‒ HR = 5.53; p = 0.02) was associated with improved disease-specific survival. Poorer disease-specific survival was observed in patients with higher primary tumor diameter (HR = 1.54; p = 0.002), higher depth of invasion (HR = 2.89; p = 0.02), invasion beyond the subcutaneous fat (HR = 5.05; p = 0.002), neck metastasis at first presentation (HR = 8.74; p < 0.001), number of positive lymph nodes (HR = 1.25; p = 0.004), and higher TNM stages (HR = 7.13; p = 0.009). Patients presenting with isolated parotid metastasis during all follow-ups had better disease-specific survival than those with neck metastasis or both (HR = 3.12; p = 0.02). Conclusion Head and neck cutaneous squamous cell carcinoma with parotid lymph node metastasis demonstrated better outcomes than cases with neck metastasis.